The New Genesis: The Greatest Experiment on Earth by Wojciech K. Kulczyk - Lloyd, Andy (Journal of Scientific Exploration, 2018)
The Universe is a complex place. Science's job is to model how nature works, and turn our understanding into something useful. Generally, this modelling works on a reductionist principle: Science is at its best when seemingly complicated processes in nature can be understood with simplifying equations and hypotheses. Where physics in concerned, this generally works out pretty well. Likewise with chemistry, notwithstanding some exceptions to the general rules. But when it comes to biology, the complexity involved seems altogether staggering. In this book, the author grapples with the disparity between the straightforward principles of evolution by natural selection, and the sheer immensity of the task when attempting to successfully apply those accepted tenets to biological processes. Wojciech Kulczyk is not convinced that evolutionary principles are capable of explaining complex forms of life. As a physicist with a PhD, he is no stranger to science. His writing is clear and erudite, demonstrating a strong grasp of many of the sciences. Yet, he remains fundamentally puzzled by the evolution of complex life on Earth, and, in particular, how it could have arisen as a matter of chance. Kulczyk considers it highly likely that the increasing complexity of life here on Earth was given a helping hand. Actually, many helping hands. He argues for an intelligence behind the design - that life needs an engineer to create the cosmic blueprint that churned out complex life on Earth. He stops short of identifying whether that intelligent designer is a spiritual entity, or a set of interested parties existing in the physical realm. Reading between the lines, he favours the latter.